Synthesis, characterization, cytotoxicity study, interaction with DNA and topoisomerase IIα of square-planar complexes with thiosemicarbazones - Thayane Paes Silva, Ludimila; Bueno Santana Pereira, George; Porto de Oliveira, Gabriela; Almeida Lima, Mauro; Honorato de Araujo-Neto, João; Olalekan Akinyemi, Amos; Alcântara Vieira, Marcelle [UNESP]; Monteiro Nascimento-Júnior, Nailton [UNESP]; Lira de Farias, Renan; Alcides Ellena, Javier; Vieira de Godoy Netto, Adelino [UNESP]; Vieira Rocha, Fillipe (Elsevier, 2024)
In this study, we report the synthesis and characterization of eight new palladium complexes and a nickel complex containing thiosemicarbazone ligands derived from chalcones and benzalketones. The techniques of Infrared and UV–visible spectroscopy, Nuclear Magnetic Resonance, Mass Spectrometry, and Elemental Analysis fully characterized the compounds. Crystallography was successful for five complexes and two ligands, allowing for X-ray Diffraction analysis. Molecular docking studies and assays involving DNA interaction via agarose gel electrophoresis and UV–Vis titration revealed no DNA interaction or inhibition of topoisomerase IIα enzyme activity. However, these compounds demonstrated potent cytotoxic effects (IC50) against breast tumor (MCF-7) and prostate (DU-145) cell lines, as well as non-tumor prostate (PNT2) cell lines. These findings highlight the relevance of structural variations and the metallic center's nature in achieving cytotoxic effects, offering insights into the development of bioactive compounds.
Keywords: ct-DNA; Cytotoxicity; Nickel(II); Palladium(II); Thiosemicarbazone; Topoisomerase